2022
DOI: 10.1007/s00213-022-06267-6
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of repeated heroin vapor inhalation during adolescence on measures of nociception and anxiety-like behavior in adult Wistar rats

Abstract: Rationale Adolescents represent a vulnerable group due to increased experimentation with illicit substances that is often associated with the adolescent period, and because adolescent drug use can result in long-term effects that differ from those caused by drug use initiated during adulthood. Objectives The purpose of the present study was to determine the effects of repeated heroin vapor inhalation during adolescence on measures of nociception, and anxie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 106 publications
4
6
0
Order By: Relevance
“…Importantly, the present study also shows that nociceptive effects of repeated opioids, which were confirmed out to ~16 weeks after the initial heroin vapor exposure in the Adolescent and Adult groups, are persistent. This is consistent with our previous work showing that repeated exposure to heroin vapor during adolescence increases baseline sensitivity to thermal stimuli and reduces the acute analgesic effects of subcutaneous heroin injections, in adulthood (Gutierrez et al 2022a). This study also extends prior results by showing that while the blunting of heroin-induced anti-nociception was present in both Adolescent-Exposed and Adult-Exposed groups, the hyperalgesic effects of the opioid antagonist naloxone were absent only in the Adolescent-Exposed group.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Importantly, the present study also shows that nociceptive effects of repeated opioids, which were confirmed out to ~16 weeks after the initial heroin vapor exposure in the Adolescent and Adult groups, are persistent. This is consistent with our previous work showing that repeated exposure to heroin vapor during adolescence increases baseline sensitivity to thermal stimuli and reduces the acute analgesic effects of subcutaneous heroin injections, in adulthood (Gutierrez et al 2022a). This study also extends prior results by showing that while the blunting of heroin-induced anti-nociception was present in both Adolescent-Exposed and Adult-Exposed groups, the hyperalgesic effects of the opioid antagonist naloxone were absent only in the Adolescent-Exposed group.…”
Section: Discussionsupporting
confidence: 93%
“…The reason for the discrepancies in prior findings is not clear, but potential causes include methodological differences, such as the stage of adolescence during which exposure occurred, dosing or testing procedures, or factors such as ambient lighting or the time of day when the behavioral testing was carried out. Our finding was particularly interesting given that we previously reported an increase in anxiety-like behavior following repeated adolescent exposure to heroin vapor (Gutierrez et al 2022a). Our studies were identical on several factors such as the dose, route of administration, age of treatment, strain of rat, etc., which limits the possible contributing factors.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations